2009
DOI: 10.3399/bjgp09x472250
|View full text |Cite
|
Sign up to set email alerts
|

Text messaging reminders to reduce non-attendance in chronic disease follow-up: a clinical trial

Abstract: This study was made possible with research funding from University of Malaya (reference F0381/2005C) and University Kebangsaan Malaysia (reference FF-225-2005) Ethics committeeMedical ethics committee -University of Malaya Medical Centre (reference 454.3) and medical ethics committeeUniversiti Kebangsaan Malaysia (reference FF-225-2005)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 18 publications
4
96
0
2
Order By: Relevance
“…In a Malaysian RCT 73 comparing the effectiveness of text messaging reminder (n = 308), telephone reminder (n = 314) and control (no reminder) (n = 309) in increasing appointment attendance in patients with chronic diseases requiring long-term follow-up, the absolute non-attendance rate for telephone reminders (13.7%) was 2% lower than with the text messaging group (15.6%). This study is limited in two regards.…”
Section: Findings From Other Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In a Malaysian RCT 73 comparing the effectiveness of text messaging reminder (n = 308), telephone reminder (n = 314) and control (no reminder) (n = 309) in increasing appointment attendance in patients with chronic diseases requiring long-term follow-up, the absolute non-attendance rate for telephone reminders (13.7%) was 2% lower than with the text messaging group (15.6%). This study is limited in two regards.…”
Section: Findings From Other Studiesmentioning
confidence: 99%
“…Two additional RCTs 66,73 investigated the differences between personal and automated reminders, but neither found any difference between the direct contact reminder and the automated reminder. In a Malaysian RCT 73 comparing the effectiveness of text messaging reminder (n = 308), telephone reminder (n = 314) and control (no reminder) (n = 309) in increasing appointment attendance in patients with chronic diseases requiring long-term follow-up, the absolute non-attendance rate for telephone reminders (13.7%) was 2% lower than with the text messaging group (15.6%).…”
Section: Findings From Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In a recent randomized trial, both text-message reminders and live telephone calls improved attendance rates for chronic disease follow-up among patients in Malaysia, with no statistically significant differences in impact between the two communication methods. 49 In Kenya, text messages to health workers significantly improved their adherence to guidelines for malaria treatment. 50 Studies on the effectiveness of SMS messages for health promotion have also shown improvements in the outcomes of care.…”
Section: Impact On Outcomes and Healthcare Costsmentioning
confidence: 99%
“…Three studies demonstrated improvements in clinic attendance with text messaging reminders versus no reminder. In three studies, [38][39][40] studied the effectiveness of an Internet-based diabetes education program with SMS and e-mail reminders and found that only 77 (39%) of the treatment arm logged-on to the online education program, and of these subjects, 34 (44%) logged-on once, 12 (16%) logged-on twice, and 31 (40%) logged-on more than three times. When subjects were asked about the number of times they logged-on, 22 (14%) stated that they had used the Web site when in fact a log-in was not recorded.…”
Section: Process Of Carementioning
confidence: 99%